Anticancer properties of Cyperus amuricus: In vitro and in silico studies targeting HEPG2 liver cancer cells via the Akt/survivin/Bcl-2 signaling pathway - Tu, Khoi Thanh; Tran, Kien Cuong; Luong, Hoa Ninh; Nguyen, Huu Thuan Anh; Nguyen, Thanh Luan; Pham, Minh Quan; Pham, Quoc Long; Pham, Thi Hai Ha (Vietnam Journal of Biotechnology, 2025)
Cyperus amuricus has been used in folk medicine to treat urolithiasis and prevent cancer. To confirm the biological activities of C. amuricus, the aim of this study is to determine and investigate the potential of anticancer activities against the HepG2 liver cancer cell line. For this purpose, the binding inhibiting activities of phenolic and flavonoid compounds docked to proteins of the Akt/survivin/Bcl-2 signaling pathway were investigated in silico and in vitro. Before analyzing the bioactivities, the crude methanol extract of C. amuricus was fractionated with various solvents. The total phenolic content (TPC) was quantified using the Folin-Ciocalteu reagent assay, whereas the total flavonoid content (TFC) was determined using the aluminum chloride assay. The MTT assay and Western blotting study were performed to determine the potential cytotoxicity of the ethyl acetate fraction (E fraction) of C. amuricus. At 221.86 ± 2.17 µg GAE/mg and 386.67 ± 4.83 µg QE/mg, the E fraction had significant levels of phenolic and flavonoid compounds. The E fraction surpassed the crude methanol extract and other fractions in terms of radical scavenger capacity with an IC50 value of 21.07 ± 0.30 µg/ml. In particular, the E fraction had high cytotoxic activity against the HepG2 cell line of hepatocellular carcinoma (IC50 = 166.50 µg/ml) but not against the standard fibroblast cell line. Western blot analysis demonstrated that the E fraction effectively induced caspase-3 activation while inhibiting the expression of Akt, survivin, and Bcl-2 in a concentration-dependent manner. Mechanistically, the molecular docking analysis results revealed that the phenolic and flavonoid compounds found in the Cyperaceae family could serve as potential phytochemicals with antioxidant and anticancer effects by targeting proteins associated with cancer proliferation. These initial findings suggested that C. amuricus could inhibit the growth of HepG2 cancer cells in vitro via the Akt/survivin/Bcl-2 signaling pathway.